An Analysis of Teacher Strategies on The Eleventh Grade Students Learning Activities in EFL Classroom at SMA Babus Salam Tangerang - Deni Iskandar; Lusiana Lusiana (LPPM Universitas Mohammad Husni Thamrin, 2019)
Research on “An Analysis of teacher’s strategies on the eleventh-grade students learning activities in EFL classroom at SMA Babus Salam” aimed at finding out the strategies that had been implemented by the English teacher related to the complexity of students in the Islamic boarding school. The approach used in this research was qualitative approach with intrinsic case study as its method. The instrument used in this research was observation and interview. The findings revealed that the English teacher did not rely on specific strategy from the particular method but she used various strategies in order to accomplish the objective of the learning. In addition, the findings also showed that the strategies had helped the students internalizing what they had learned into a real practice. Also, the strategies have provided them with sufficient exposure and opportunity to practice the target language and to accomplish the objective of the learning.